Catalytic Epoxidation of Olefins by Nanolayered Polyoxomolybdate [4,4´-H2bipy][Mo7O22].(H2O) - A. Abbasi; M. Najafi; M. Masteri-Farahani; V. H. Rodrigues (Journal of Sciences, Islamic Republic of Iran)
A two-dimensional nanolayered polyoxomolybdate, [4,4´-H2bipy] [Mo7O22].H2O (1), where 4,4´-bipy = 4,4´-bipyridine, was prepared and characterized by FT-IR and atomic absorption spectroscopies, transmission electron microscopy (TEM), X-ray single crystal and powder diffraction (XRD), and thermogravimetric analysis. The catalytic performance of 1 was assessed in the epoxidation of some olefins employing tert-butyl hydroperoxide (TBHP) as oxidant and acetonitrile as solvent. Compound 1 showed moderate to excellent activity and selectivity towards the epoxidation of the olefins. Thermal, structural and catalytic stability of 1 as well as its reusability were examined. The effect of the catalyst amount and the nature of solvent on the activity of 1 were also investigated.